PENGARUH KEBIJAKAN HUTANG, KEBIJAKAN DIVIDEN, DAN INVESTASI TERHADAP NILAI PERUSAHAAN - Siti Aisyah; Faisal Umardani Hasibuan; Andarias Patiran; Yohanes Marani; Abdul Rosid (POLITEKNIK LP3I JAKARTA, 2025)
This study aims to determine the effect of debt policy, dividend policy, and investment policy both simultaneously and partially on the value of public companies listed on the Indonesia Stock Exchange in 2019-2023. The population is 18 companies and the sample taken is 6 companies. The type of analysis uses associative analysis with the classical assumption method, multiple linear regression, and hypothesis testing. The results of this study indicate that debt policy, dividend policy, and investment policy simultaneously have a significant effect on company value. Then partially, debt policy does not have a significant effect on company value. While dividend policy and investment policy have a significant effect on company value.